2011
DOI: 10.1111/j.1365-2885.2011.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tildipirosin in bovine plasma, lung tissue, and bronchial fluid (from live, nonanesthetized cattle)

Abstract: The pharmacokinetics of tildipirosin (Zuprevo(®) 180 mg/mL solution for injection for cattle), a novel 16-membered macrolide for treatment, control, and prevention of bovine respiratory disease, were investigated in studies collecting blood plasma, lung tissue, and in vivo samples of bronchial fluid (BF) from cattle. After single subcutaneous (s.c.) injection at 4 mg/kg body weight, maximum plasma concentration (C(max)) was 0.7 μg/mL. T(max) was 23 min. Mean residence time from the time of dosing to the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 26 publications
8
70
5
2
Order By: Relevance
“…For fluoroquinolones, all strains are classified as intermediate. Breakpoints are not available for gamithromycin and tildipirosin, but the MIC 50 (128 µg/mL) is much greater than the maximum concentrations used for respiratory infections at therapeutic doses, 18 and 15 µg/g of lung homogenate, respectively [35], [36].…”
Section: Resultsmentioning
confidence: 99%
“…For fluoroquinolones, all strains are classified as intermediate. Breakpoints are not available for gamithromycin and tildipirosin, but the MIC 50 (128 µg/mL) is much greater than the maximum concentrations used for respiratory infections at therapeutic doses, 18 and 15 µg/g of lung homogenate, respectively [35], [36].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the difficulty in determining the free drug concentration at the target site, the PK data in most previous PK-PD studies have often been obtained from plasma. It has been shown that the antibiotic concentration time-course in plasma is significantly different from that in biophase at the infection site, including the interstitial fluid (ISF) and epithelial lining fluid (ELF) 2729 . Therefore, it is necessary to determine the active concentration of free antimicrobial drugs at the target site using PK-PD modeling to achieve a rational dosage regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Tildipirosin has been approved for parenteral treatment of respiratory disease in cattle and swine (EMA, 2010). This macrolide antibiotic is rapidly absorbed and extensively distributed to tissues where they achieve multifold higher concentrations relative to those observed in pigs and cattle plasma samples (Anadon & Reeve-johnson, 1999;Norcia et al, 2004).Due to the extensive use of TD, several studies on the pharmacokinetics, pharmacodynamics, particularly, distribution, and metabolism have been conducted in various species, including pigs (Rose et al, 2013;Torres et al, 2016) and cattle (Menge et al, 2012). In pigs, it is postulated that the metabolism of tildipirosin proceeds by reduction and sulfate conjugation with subsequent hydration (or ring opening), by demethylation, by dihydroxylation, and by S-cysteine and S-glutathione conjugation (EMA, 2015).…”
mentioning
confidence: 99%